Pengembangan Sistem Informasi Manajemen Lembaga Penelitian UNM - Muhammad Dinar; Fathahillah Fathahillah (Seminar Nasional LP2M UNM, 2019)
The focus of this research is the development of an integrated management information system for UNM research institutions. The aim of this research is to develop an integrated information system to improve and assist the performance of UNM research institutions. This type of research is research and development (Research and Development), with the System Development Life Cycle (SDLC) method. The planned research will develop an integrated management information system that can be implemented to support performance at UNM research institutions.